Survival outcomes of patients with head and neck squamous cell cancer with hepatitis B virus infection: An analysis from an endemic tertiary center - Cheng‐Lun Lai; Cheng‐Hsien Lin; Yu‐Chen Su; Yu‐Hsuan Shih; Chen‐Chi Wang; Chieh‐Lin Jerry Teng; Cheng‐Wei Chou (Cancer Medicine, 2023)
Abstract Background Hepatitis B virus (HBV) affects the occurrence and survival outcome of various malignant disorders. The study aimed to evaluate the survival outcome of head and neck squamous cell cancer (HNSCC) patients with or without HBV infection. Methods This study included patients with HNSCC who visited Taichung Veterans General Hospital from 2007 to 2015. HBV infection was defined by hepatitis B surface antigen (HBsAg) seropositivity. By propensity score matching, we compared survival outcomes, including progression‐free survival (PFS) and overall survival (OS), among patients with or without HBV infection. Results The prevalence of HBV infection in our cohort was 12.3%. Among the 1,015 patients included in the matched analysis, a higher risk of baseline liver cirrhosis (11.3% vs. 3.4%, p < 0.001) and initial hepatic dysfunction (10.8% vs. 5.4%, p = 0.005) rates were observed than those without HBV infection at baseline. The 5‐year OS was 43.1% and 53.2% (p < 0.001) and the 5‐year PFS was 37.4% and 42.3% (p = 0.007) in patients with and without HBV infection, respectively. The incidence of subsequent hepatic dysfunction showed no difference between patients with and without HBV infection (29.6% vs. 26.8%, p = 0.439). Conclusions Patients with HNSCC and HBV infection were younger and had a higher risk of cirrhosis compared to those without HBV infection. Moreover, HBV infection significantly influenced the OS and PFS outcomes but not subsequent hepatic dysfunction in patients with HNSCC.